1998
DOI: 10.1038/sj.bjp.0701686
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of N‐benzoyl‐D‐phenylalanine and related compounds with the sulphonylurea receptor of β‐cells

Abstract: 1 The structure activity relationships for the insulin secretagogues N-benzoyl-D-phenylalanine (NBDP) and related compounds were examined at the sulphonylurea receptor level by use of cultured HIT-T15 and mouse pancreatic b-cells. The a nities of these compounds for the sulphonylurea receptor were compared with their potencies for K ATP -channel inhibition. In addition, the e ects of cytosolic nucleotides on K ATP -channel inhibition by NBDP were investigated. 2 NBDP displayed a dissociation constant for bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…In addition, an increase in plasma insulin concentration has been reported following the intravenous infusion of free amino acids in both healthy (7)(8)(9) and type 2 diabetic subjects (10). In accordance, various in vitro studies using incubated ␤-cells of the pancreas have described strong insulinotropic effects of arginine, leucine, and phenylalanine (11)(12)(13)(14)(15)(16)(17)(18). Recently, we performed a series of studies in which we determined the in vivo insulinotropic potential of various free amino acids and protein (hydrolysates) when ingested in combination with carbohydrates in healthy young subjects (19 -21).…”
mentioning
confidence: 63%
“…In addition, an increase in plasma insulin concentration has been reported following the intravenous infusion of free amino acids in both healthy (7)(8)(9) and type 2 diabetic subjects (10). In accordance, various in vitro studies using incubated ␤-cells of the pancreas have described strong insulinotropic effects of arginine, leucine, and phenylalanine (11)(12)(13)(14)(15)(16)(17)(18). Recently, we performed a series of studies in which we determined the in vivo insulinotropic potential of various free amino acids and protein (hydrolysates) when ingested in combination with carbohydrates in healthy young subjects (19 -21).…”
mentioning
confidence: 63%
“…These moieties effectively block K ATP channels regardless of which side of the membrane they are applied, suggesting that they can diffuse through the plasma membrane [27]. These channels are not just blocked by sulphonylureas; compounds such as benzoic acid derivatives and N-acylphenylalanine derivatives act as inhibitors by interaction with SUR [28][29][30]. Although it has been reported that these drugs act on plasma membrane channels, their effect on intracellular K ATP channels and sulphonylurea receptors remains to be specifically addressed.…”
Section: Plasma Membrane K Atp Channels In the Pancreatic β β β β-Cellmentioning
confidence: 96%
“…Interestingly, the benzamido group alone is also likely to interact with SUR1, since a benzoic acid derivative of glibenclamide and meglitinide (Table 1) has been shown to induce insulin release (Henquin et al, 1987). Thus it seems plausible that the concerted interaction with the meglitinide-and tolbutamide-binding sites probably accounts for the several thousand-fold increase in affinity of glibenclamide equipped with both a benzamido (5-chloro-N-ethylen-2-methoxy benzamide) (Figures 1 and 3, region C) and a sulphonylurea moiety (region D) vs. tolbutamide equipped with a sulphonylurea moiety, only (Figure 1; Schwanstecher et al, 1998;Ashfield et al, 1999). Glimepiride is characterized by a slightly yet significantly lower binding affinity to β-cell membranes than glibenclamide (Müller et al, 1994a; see Table 1).…”
Section: Discussionmentioning
confidence: 94%